22 nights - Jones, Linda Winstead (New York : Berkley Sensation, 2008)
'Just when the lovely Belavalari has given up on Merin--the dashing general to whom she lost her maidenhead--he appears in her native village, with orders from the emperor to return with Bela as a prospective empress. Fearless and skilled with her magical sword, Bela embodies everything Merin could want in a soldier. Except that she's female. And already married--he's horrified to learn--to him...'--p. [4] of cover
Keywords: Soldiers -- fiction; Magic -- Fiction; Man-woman relationships -- Fiction